Meningkatkan Kesejahteraan Masyakarat Dusun Srikoyo Melalui Pemberdayaan SDM dan Pengembangan UMKM - Pratama, Yuda; Putri, Imael Maelani; Imaniyya, Najma Wahida; Nabila, Zalwa Lutfiatu; Khairul, Muhammad Afnan Mardhi; Kemal, Dimas Raffi Arya; Adani, Kindana Wira; Ni’ammah, Ummah Qudrotun; Kurniawan, Muhamad Dary Farhan; Pefrina, Octisha Nia; Wirasenjaya, Ade Marup (Universitas Muhammadiyah Yogyakarta, 2025)
Padukuhan Srikoyo which is located in Playen District, Gunungkidul, has local-based economic potential which includes the production of thiwul, herbal medicine, mushroom cultivation, as well as corn and rice farming. However, society still faces challenges in digital marketing of business results, product processing innovation, and suboptimal utilization of agricultural waste. The community service team is here with an initiative to empower the local economic sector which aims to increase community knowledge and skills in digitalizing and branding Micro, Small and Medium Enterprises (MSMEs) products. Apart from that, this program also aims to increase farmers' knowledge and skills regarding innovations in processing corn products and processing corn waste. The methods applied include outreach and assistance to business actors and farmer groups to improve their skills in online marketing and managing agricultural by-products. The results of this program show that business actors have a better understanding of effective marketing strategies by utilizing social media and are able to create attractive content and product photos to upload on digital platforms. Apart from that, farmer groups gained new insight into the use of corn waste as animal feed and organic fertilizer, so that they could increase the added value of their agricultural products. With this program, it is hoped that business actors and farmer groups in Srikoyo Hamlet can develop more competitively and sustainably, so as to improve the economic welfare of the local community.